Possibilities of the carte de visite in the visual discourse on the French intervention and the second empire (Enlace UIC: Revista de Investigación de la División de Posgrados de la Universidad Intercontinental, 2023)
Patented by the French photographer André Adolphe Disderi in the mid-19th century, the carte de visite or business card soon became the most popular form of portrait. The novelty of this format consisted, besides its small size (6 x 9 cm), in its mass production and its low cost, which was considerably lower than that of a painting or a simple daguerreotype. Disderi achieved the definitive popularity of photography, as he opened the possibility of making them accessible to those who lived less comfortably. For the taking of these portraits, Disderi adjusted a special type of camera equipped with four lenses that operated simultaneously or in rapid succession; thus, with the use of a single shot, from which a set of photographs was obtained. The technique applied in the making of these portraits was at first the wet collodion, whose qualities responded to the need to use short exposure times; later the dry plate was adopted. Portraits were mostly printed on albuminated paper, a support commonly used in the photographs that were taken during almost the entire 19th century, the demand for carte de visite would spread throughout the world. In Mexico these photographic records were made from the early 1860s until around the 1910s.
Keywords: photography; 19th Century; collecting; social function